2018
DOI: 10.3390/w10020224
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Water Security in Kathmandu Valley before and after Water Transfer from another Basin

Abstract: Kathmandu Upatyaka Khanepani Limited (KUKL) has planned to harness water from outside the valley from Melamchi as an inter-basin project to supply water inside the ring road (core valley area) of the Kathmandu Valley (KV). The project, called the "Melamchi Water Supply Project (MWSP)", is expected to have its first phase completed by the end of September 2018 and its second phase completed by the end of 2023 to supply 170 MLD (million liters a day) through the first phase and an additional 340 MLD through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 21 publications
0
25
0
1
Order By: Relevance
“…The boundary of productive aquifer systems is outlined by the three KVWSMB groundwater districts with the new KUKL water supply service area located mostly in the central district ( Figure 1). The population in the valley has increased from 1.1 million in 1991 to 1.6 million in 2001 to 2.5 million in 2011 (CBS, 2003(CBS, , 2014a, which increased the water demand from 155 to 370 mld (Thapa et al, 2016a(Thapa et al, , 2016b(Thapa et al, , 2018. Agricultural lands in the valley have decreased from 62% to 42% between 198442% between and 200042% between (ICIMOD, 2007.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…The boundary of productive aquifer systems is outlined by the three KVWSMB groundwater districts with the new KUKL water supply service area located mostly in the central district ( Figure 1). The population in the valley has increased from 1.1 million in 1991 to 1.6 million in 2001 to 2.5 million in 2011 (CBS, 2003(CBS, , 2014a, which increased the water demand from 155 to 370 mld (Thapa et al, 2016a(Thapa et al, , 2016b(Thapa et al, , 2018. Agricultural lands in the valley have decreased from 62% to 42% between 198442% between and 200042% between (ICIMOD, 2007.…”
Section: Study Areamentioning
confidence: 99%
“…The KVWSMB groundwater districts are surrounded by low-permeability fractured rock formations and the outer periphery (hilly area) of the valley is covered by mixed forest. In the valley, the peri-urban area is partly agricultural and partly built up, while the central part of the valley is covered by built-up urban areas (Thapa et al, 2016a(Thapa et al, , 2016b(Thapa et al, , 2018. The northern groundwater district (NGD) is situated on top of coarse unconsolidated deposits, which have high permeability and the highest potential for groundwater abstraction (Figure 1).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The access to piped water had declined from 68% to 58% from 2003 to 2014 [11], and the Kathmandu Valley reported grossly inadequate and unreliable water supply services, where 4 million residents lived with 4.7% annual growth [12]. The Kathmandu Upatyaka Khanepani Limited has sole authority to distribute water in the urban areas of the Kathmandu Valley, but supplies only 19% of the total water demand during the dry season and 31% in the wet season in the service areas [13]. Aihara et al (2015) showed the daily averaged water collection from the piped water was 15.4 LPCD (liters per capita per day), as lowest as <4 h/week supply [14].…”
Section: Introductionmentioning
confidence: 99%